Analisis gugus fungsi pada polimer polyethylene glycol (PEG) coated-nanopartikel oksida besi hitam (Fe3O4) dan biomolekul - Alfrie Musa Rampengan (Jurnal Kimia Fullerene, 2017)
A study has been conducted for functional group analysis of polyethylene Glycol (PEG) coated nanoparticles of iron oxide (Fe3O4) and biomolecules using FTIR-Spectroscopy. A sample functional group analysis was performed to determine the ability of modified iron oxide nanoparticles (Fe3O4) with the addition of PEG polymers, potentially to bind biomolecules. The presence of water molecules absorption on the surface of black iron oxide nanoparticles (Fe3O4) causing bonding with PEG polymer is indicated by the absorption peak at the vibration of the -OH (hydroxyl) group at the wave number 3441,01 cm-1. The result of modification of black iron oxide nanoparticles (Fe3O4) with PEG, can bind biomolecules exhibited repetition of the absorption peak on the vibration of the -OH (hydroxyl) group at wave number 3433,29 cm-1 and even the appearance of a new absorption peak on vibration CO at wave number 1350,17 cm-1